Avaliação da qualidade dos frutos de genótipos de aroeira (Schinus terebinthifolia Raddi.) em diferentes estádios de maturação - Gerhardt, Nataly Senna (2018)
Schinus terebinthifolia (aroeira) is a species that has attracted the interest of many farmers because the fruits are used as condiment, being of interest to the food industry, and for the potential benefits of its essential oil. This high popularity demands fruit quality, in both its physical and chemical characteristics. In the present study, the quality of the fruits of various genotypes of aroeira in different stages of maturation was evaluated, with the aim of determining the best period for the harvest to meet the market demand. The fruits of the genotype BAAr 05, were analyzed in the five maturation stages: green fruit (1); green-pink fruit (2); pink fruit (3); "ripe" red fruit (4); intense red fruit "past-ripe" (5), analyzing the physical characteristics (weight, size), and chemical characteristics (chemical components of the essential oil and its yield), and developing a new methodology for headspace analysis. The genotypes BAAr 05, BAAr 08-C and BAAr 23, were evaluated in the fifth maturation stage and identified according to chemo-types. The experimental design was completely randomized, with three replications. The results were submitted to chemometrics to perform the multivariable analysis of the data, using the principal components analysis (PCA). The maturation stages of the BAAr 05 genotype showed the grouping between uniform stages and separation between the intermediate stages, showing the transition characteristic of the fruits in stages 2 and 3. The Clevenger apparatus was used to determine the oil yield, which reaches its peak in the fourth stage of maturation(3,76%). This suggests that the fourth stage is the best harvesting time. The PCA analysis showed grouping between the repetitions of the genotypes BAAr 05, BAAr 08-C and BAAr 23, demonstrating that the genotypes have differentiated chemotypes. It became clear that the headspace technique excels in chemometric analysis of the main components also analyzing the genotype chemotypes.